Anda di halaman 1dari 16

FACULTY OF TECHNOLOGY

Department of Engineering Mathematics

Bachelor of Science in Civil Engineering

Year II (2009/2010)

Semester I

EMT 2101: Engineering Mathematics III

Lecture Set Three : Part Two

Laplace Transform of Derivates, Solutions of Laplace


Differential Equations by use of Laplace Transforms

2008
LAPLACE TRANSFORMS OF DERIVATIVES

Theorem 6: If L { f (t )} = F ( s ) , then L { f
(t )} = sF ( s ) - f (0) .

Proof: Let f
(t ) denote the first derivative of f (t ). Then, by definition,

L{ f
(t )} =
e- st f
(t ) dt.
0

dv du
Setting u = e - st and = f
(t ), so that = - se - st and v = f (t ), and invoking the
dt dt
formula for integration by parts to perform the integrand on the bright-hand
side, we have


L{ f
(t )} =
e - st f (t )
+ s
e - st f (t )dt .
0
0
- st
But since lim = 0 , because s > 0 and large enough to ensure that the
e f (t )
t

decay of the exponential function e - st overshadows any growth characteristic of


f (t ), and at the same time lim e - st f (t )
= f (0) , there follows that the integrated
t 0

part yields only - f (0). Therefore, we are left with the expression

L{ f
(t )} = - f (0) + s
e - st f (t )dt .
0

If then we recognise that the remaining integral is in fact the Laplace


transform of f (t ) ,there immediately follows that
L{ f
(t )} = sF ( s) - f (0),
which confirms our assertion.

Using the Laplace transform notation then, we have


L{ f
(t )} = sL { f (t )} - f (0).
If we need to find the Laplace transform of the second derivative we simply
replace f (t ) by f
(t ) and f
(t ) by f
(t ) .
L{ f
(t )} = sL { f
(t )} - f
(0).
Inserting the already established expression L { f (t )} = sF ( s) - f (0), we then find
that
L{ f
(t )} = s
s L { f (t )} - f = s L { f (t )} - sf (0) - f
(0). 2
(0).
By similar procedures, we find the
L{ f
(t )} = s 3 L { f (t )} - s 2 f (0) - sf
(0) - f (0).
L { f ( iv ) (t )} = s 4 L { f (t )} - s3 f (0) - s 2 f
(0) - sf
(0) - f


(0).
L { f ( v ) (t )} = s 5 L { f (t )} - s 4 f (0) - s 3 f
(0) - s 2 f
(0) - sf
(0) - f (iv ) (0).


and so on. In general, we find that
n
L { f ( n ) (t )} = s n L { f (t )} - s n - k f ( k -1) (0)
k =1

where f (0)
(0) = f (0).

2
The above results or formulae are very fundamental in the solution of
differential equations. Thus if we let
dx d2x dnx
x t =0 = x0 , = x1 , = x2 , , = xn
dt t =0 dt 2 t =0 dt n t =0
with L { f (t )} = X , then we have
L{ f
(t )} = sX - x0 .
L{ f
(t )} = s 2 X - sx0 - x1 ,

L{ f
(t )} = s 3 X - s 2 x0 - sx1 - x2 ,


L { f ( iv ) (t )} = s 4 X - s 3 x0 - s 2 x1 - sx2 - x3 ,
L { f ( v ) (t )} = s 5 X - s 4 x0 - s 3 x1 - s 2 x2 - sx3 - x4 ,
and so on. In general, therefore,
n
L { f ( n ) (t )} = s n X - s n - k xk -1 .
k =1
Exercises:
a) Find L { sin(bt - a )} ;
b) Find L { cos(at + a )}
Find L { e ( cos t + 6sin t ) }
-2 t
c)
1 1
d) Find L sin at - cos bt
a b

SOLUTIONS OF DIFFERENTIAL EQUATIONS BY USE OF LAPLACE


TRANSFORMS

In solving differential equations by use of Laplace transforms, four distinct


steps are followed:
1. The differential equation in question is written in terms of its Laplace
transform,
2. The initial conditions are inserted or applied,
3. The transform equation is re-arranged to give the transform of the
solution,
4. The inverse of the transform of the solution is determined.

Given a function f (t ) , we recall that the Laplace transforms of the derivatives


of the various orders of this solution are given by:
L{ f
(t )} = sF ( s ) - f (0)
L{ f
(t )} = s 2 F ( s ) - sf (0) - f
(0),
L{ f
(t )} = s 3 F ( s ) - s 2 f (0) - sf

(0) - f

(0),
L { f ( iv ) (t )} = s 4 F ( s ) - s3 f (0) - s 2 f
(0) - sf
(0) - f


(0),
and so on, such that in general we have
n
L { f ( n ) (t )} = s n F (s ) - s n -k f ( k -1) (0), n = 1, 2,3, K
k =1
We need to develop a convenient notation for solving differential equations
using Laplace transforms. For the function f (t ) , let

3
x = f (t ) ,
L { f (t )} = F ( s) = X ,
and for the initial conditions at t = 0, let
dx d2x d3x
xt =0 = x0, = x1 , = x2 , = x3 ,
dt t =0 dt 2 t =0 dt 3 t =0
and so on, such that
dnx
= xn , n = 0,1, 2,K
dt n t =0
Accordingly, therefore, let us set
f (0) = x0 , f (0) = x1 , f (0) = x2 , (0) = x3 ,
f


such that, in general,
f ( n ) (0) = xn , n = 0,1, 2,K

With these notations, we then have


L{ f
(t )} = sX - x0 ,
L{ f
(t )} = s 2 X - sx0 - x1 ,

L{ f
(t )} = s 3 X - s 2 x0 - sx1 - x2 ,


and so on, such that in general we have
n
L { f ( n ) (t )} = s n X - s n - k xk -1 , n = 1, 2,3,K
k =1
Note the following features when we are writing the n - th derivative:
1. the first term is s n X ,
2. the powers of s then decrease with succeeding terms,
3. all terms after the first are negative,
4. the subscripts increase in order of x0 , x1 , x2 , x3 ,L

dx
Example 1: Solve - 4 x = 8 , given that x = 2 at t = 0.
dt
A convenient notation would of course have been x&- 4 x = 8 , x = 2 at t = 0.

Step 1: Re-write the entire equation in terms of Laplace transforms:


dx
L - 4L { x} = L { 8}
dt
or
8
sX - x0 - 4 X =
s
Step 2: Insert the initial condition 0 x = 2 :
8
sX - 2 - 4 X =
s
so that we have
8
( s - 4) X = + 2
s
Step 3: Re-arrange to make X the subject of the expression:

4
8 2
X = +
s ( s - 4) ( s - 4)
Step 4: Take the inverse transform of X :
8
First break X = into partial fractions as
s ( s - 4)
8 A B
= +
s ( s - 4) s s - 4
where using Cover-up Rule, we have
8 8
A = lim s = lim = -2,
s 0 s ( s - 4) s 0 ( s - 4)
and
8 8
B = lim( s - 4) = lim = 2,
s 4 s ( s - 4) s 4 s
Thus
4 2
X = - .
s-4 s
Taking the inverse transform, we thus find that
x = 4e 4t - 2.

dx
Example 2: Solve 2 + 3x = e 4t , given that x = 5 at t = 0.
dt
Let us convenient write the equation as
2 x&+ 3 x = e 4t , with x = 5 at t = 0.

Step 1: Express the equation in terms of Laplace transforms:


dx
2L + 3L { x} = L { e 4t }
dt
or
1
2 sX - 2 x0 + 3 X = .
s-4
Step 2: Insert the initial condition x0 = 5 :
1
2 sX - 10 + 3 X = .
s-4
so that we have
1
(2 s + 3) X = + 10.
s-4
Step 3: Re-arrange to make X the subject of the expression:
1 10
X = + .
( s - 4)(2 s + 3) 2 s + 3
Note that the second term on the right can be expressed as
10 5
= .
2 s + 3 s + (3 / 2)
The first term on the right can be split into partial fractions as
1 A B
= + ,
( s - 4)(2 s + 3) s - 4 2 s + 3
whence, by the cover-up rule, we have

5
1 1 1
A = lim( s - 4) = lim = ,
s 4 (2 s + 3)( s - 4) s 4 (2 s + 3) 11
and
1 1 2
B = lim (2 s + 3) = lim =- .
s - (3 / 2) (2 s + 3)( s - 4) s - (3 / 2) ( s - 4) 11
Hence,
1 1 1 1 5
X = - + .
11 s - 4 11 s + (3 / 2) s + (3 / 2)
Step 4: Take the inverse transform of X :
1 1 1
x = e 4t - e - (3 / 2) t + 5e- (3 / 2)t = ( 54e- (3 / 2) t + e4 t ) = f (t ).
11 11 11

dx
Example 3: Solve 2 + 5 x = e -2t , given that x = 1 at t = 0.
dt
Let us convenient write the equation as
2 x&+ 5 x = e -2t , with x = 3 at t = 0.

Step 1: Express the equation in terms of Laplace transforms:


dx
2L + 5L { x} = L { e -2t }
dt
or
1
2 sX - 2 x0 + 5 X = .
s+2
Step 2: Insert the initial condition x0 = 1:
1
2 sX - 2 + 5 X = .
s-4
so that we have
1
(2 s + 5) X = + 2.
s+2
Step 3: Re-arrange to make X the subject of the expression:
1 2
X = + .
( s + 2)(2s + 5) 2 s + 5
Note that the second term on the right can be expressed as
2 1
= .
2 s + 5 s + (5 / 2)
The first term on the right can be split into partial fractions as
1 A B
= + ,
( s + 2)(2 s + 5) s + 2 2s + 5
whence, by the cover-up rule, we have
1 1
A = lim ( s + 2) = lim = 1,
s -2 (2 s + 5)( s + 2) s - 2 (2 s + 5)
and
1 1
B = lim (2 s + 5) = lim = -2.
s - (5 / 2) (2 s + 5)( s + 2) s - (5 / 2) ( s + 2)
Hence,

6
1 1 1 1
X = - + =
s + 2 s + (5 / 2) s + (5 / 2) s + 2
Step 4: Take the inverse transform of X :
x = f (t ) = e -2t .

dx
Example 4: Solve 3 - 4 x = sin 2t , given that x = 1/ 3 at t = 0.
dt
Let us conveniently write the equation as
3 x&- 4 x = sin 2t , with x = 1/ 3 at t = 0.

Step 1: Express the equation in terms of Laplace transforms:


dx
3L - 4L { x} = L { sin 2t}
dt
or
2
3sX - 3 x0 - 4 X = 2 .
s +4
Step 2: Insert the initial condition x0 = 1/ 3 :
2
3sX - 1 - 4 X = 2 .
s +4
so that we have
2
(3s - 4) X = 2 + 1.
s +4
Step 3: Re-arrange to make X the subject of the expression:
2 1
X = 2 + .
( s + 4)(3s - 4) 3s - 4
Note that the second term on the right can be expressed as
1 1/ 3
= .
3s - 4 s - (4 / 3)
The first term on the right can be split into partial fractions as
2 A Bs + C
= + 2 .
( s + 4)(3s - 4) 3s - 4 s + 4
2

Using the cover-up rule, we have


2 2 18 9
A = lim (3s - 4) = lim 2 = = ,
s 4 / 3 (3s - 4)( s + 4) s 4 / 3 ( s + 4) 52 26
2

Noting now that


2 9 (Bs + C )
= + 2 ,
( s + 4)(3s - 4) 26(3s - 4) ( s + 4)
2

or
2 (9 / 26)( s 2 + 4) + ( Bs + C )(3s - 4)
= .
( s 2 + 4)(3s - 4) ( s 2 + 4)(3s - 4)
Multiplying out the numerator on the right-hand side and collecting
coefficients of powers of s , we have
2 [(9 / 26) + 3B) s 2 + (3C - 4 B) s + [18 /13 - 4C )
= .
( s 2 + 4)(3s - 4) ( s 2 + 4)(3s - 4)
Equating coefficients of powers of s on both sides, we get the system of
equations:

7
(9 / 26) + 3B = 0,
18 /13 - 4C = 2,
3C - 4 B = 0.
3
From the first equation, we have B = - . From the second equation we
26
2
have C = - .
13
With these values of the coefficients, the transform equation becomes:
2 9 (3s + 4)
= - ,
( s + 4)(3s - 4) 26(3s - 4) 26( s 2 + 4)
2

or
2 3 1 3 s 4
= - - ,
( s + 4)(3s - 4) 26 s - (4 / 3) 26 s + 4 26( s 2 + 4)
2 2

Therefore,
1 2
X = + 2
3s - 4 ( s + 4)(3s - 4)
1 1 3 1 3 s 4
= + - -
3 s - (4 / 3) 26 s - (4 / 3) 26 s + 4 26( s 2 + 4)
2

35 1 3 s 4
= - - .
78 s - (4 / 3) 26 s + 4 26( s 2 + 4)
2

Hence, taking the inverse Laplace transform, we get


35 1
x(t ) = e(4 / 3) t - ( 3cos 2t - 2sin 2t ) .
78 26

d2x dx
Example 5: Solve - 4 x = cos 2t , , given that x = 2, = 3 at t = 0.
dt 2
dt
dx
x&- 4 x = cos 2t , x = 2,
A convenient notation would of course have been & = 3 at
dt
t = 0.

Step 1: Re-write the entire equation in terms of Laplace transforms:


d 2 x
L 2 - 4L { x} = L { cos 2t}
dt
or
s
s 2 X - sx0 - x1 - 4 X = 2
s +4
Step 2: Insert the initial condition x0 = 2 and x1 = 3
s
s 2 X - 2s - 3 - 4 X = 2
s +4
so that we have
s
( s 2 - 4) X = 2 + 2s + 3
s +4
Step 3: Re-arrange to make X the subject of the expression:

8
s s 3
X = +2 2 + 2
2
( s + 4)( s - 4)
2
s -4 s -4
Step 4: Take the inverse transform of X :
s
First break 2 into partial fractions as
( s + 4)( s 2 - 4)
s As + B C D
= 2 + + .
( s + 4)( s - 4) s + 4 s + 2 s - 2
2 2

On gathering the right-hand side over the same denominator, we have


s ( A + C + D)s 3 + ( B - 2C + 2 D) + 4(C - A + D)s + 2( D - C - 2 B )
= .
( s 2 + 4)( s 2 - 4) ( s 2 + 4)( s 2 - 4)
Upon equating the coefficients of the various powers of s in numerators, we
get
A + C + D = 0,
B - 2C + 2 D = 0,
4(C - A + D) = 1,
2( D - C + 2 B ) = 0.
Solving this system of equations, we find that
1 1 1
A = - , B = 0, C = , D = .
8 16 16
Hence
s 1 s 1 1
=- 2 + + .
( s + 4)( s - 4)
2 2
8 s + 4 16( s + 2) 16( s - 2)
and
3 2s 1 s 1 1
X = 2 + 2 - 2 + + .
s - 4 s - 4 8 s + 4 16( s + 2) 16( s - 2)
Therefore
3 17 1
x(t ) = sinh 2t + cosh 2t - cos 2t.
2 8 8

d2x dx dx
Example 6: Solve - 3 + 2 x = 0, given that x = 4, = 3 at t = 0.
dt 2
dt dt

Step 1: Re-write the entire equation in terms of Laplace transforms:


d 2 x dx
L 2 - 3L + 2L { x} = 0.
dt dt
or
s 2 X - sx0 - x1 - 3sX + 3x0 + 2 X = 0
Step 2: Insert the initial condition x0 = 4 and x1 = 3
s 2 X - 4 s - 3 - 3sX + 12 + 2 X = 0
so that we have
( s 2 - 3s + 2) X - 4 s + 9 = 0
Step 3: Re-arrange to make X the subject of the expression:
4s - 9 4s - 9
X = 2 =
s - 3s + 2 ( s - 2)( s - 1)

9
Step 4: Take the inverse transform of X :
4s - 9
First break into partial fractions as
( s - 2)( s - 1)
4s - 9 A B
= + .
( s - 2)( s - 1) s - 2 s - 1
On gathering the right-hand side over the same denominator, we have
4s - 9 ( A + B) s - ( A + 2 B )
= .
( s - 2)( s - 1) ( s - 2)( s - 1)
Upon equating the coefficients of the various powers of s in numerators, we
get
A + B = 4,
A + 2 B = 9.
Solving this system of equations, we find that
A = -5, B = 9.
Hence
5 9
X =- + .
s - 2 s -1
and therefore
x(t ) = 9et - 5e 2t .

d2x dx dx
Example 7: Solve - 7 + 12 x = 2, given that x = 1, = 5 at t = 0.
dt 2
dt dt

Step 1: Re-write the entire equation in terms of Laplace transforms:


d 2 x dx
L 2 - 7L + 12L { x} = 0.
dt dt
or
2
s 2 X - sx0 - x1 - 7 sX + 7 x0 + 12 X =
s
Step 2: Insert the initial condition 0 x = 1 and x1 = 5
s X - s - 5 - 7 sX + 7 + 12 X = 0
2

so that we have
2 s 2 - 2s + 2
( s - 7 s + 12) X = + s - 2 =
2

s s
Step 3: Re-arrange to make X the subject of the expression:
s 2 - 2s + 2 s 2 - 2s + 2
X = =
s ( s 2 - 7 s + 12) s ( s - 4)( s - 3)
Step 4: Take the inverse transform of X :
s 2 - 2s + 2
First break into partial fractions as
s ( s - 4)( s - 3)
s 2 - 2s + 2 A B C
= + +
s ( s - 4)( s - 3) s s - 4 s - 3
Using the cover-up rule, we have
s 2 - 2s + 2 s 2 - 2s + 2 1
A = lim s = lim = ,
s 0 s ( s - 4)( s - 3) s 0 ( s - 4)( s - 3) 6

10
s 2 - 2s + 2 s 2 - 2 s + 2 10 5
B = lim( s - 4) = lim = = ,
s 4 s ( s - 4)( s - 3) s 4 s ( s - 3) 4 2
s 2 - 2s + 2 s 2 - 2s + 2 5
C = lim( s - 3) = lim = ,
s 3 s ( s - 4)( s - 3) s3 ( s - 4) s 3
Hence
11 5 1 5 1
X = + - .
6 s 3 s -4 2 s -3
and therefore
1 5 4 t 5 3t
x(t ) = + e - e .
6 2 3

d2x dx dx
Example 8: Solve - 6 + 8 x = e 3t
, given that x = 0, = 2, at t = 0.
dt 2 dt dt

Step 1: Re-write the entire equation in terms of Laplace transforms:


d 2 x dx
L 2 - 6L + 8L { x} = L { e3t } .
dt dt
or
1
s 2 X - sx0 - x1 - 6 sX + 6 x0 + 8 X =
s -3
Step 2: Insert the initial condition 0 x = 0 and x 1 = 2
1
s 2 X - 2 - 6sX + 8 X = ,
s-3
so that we have
1
( s 2 - 6 s + 8) X = + 2.
s -3
Step 3: Re-arrange to make X the subject of the expression:
s 2 - 2s + 2 2s - 5
X = 2 =
( s - 6 s + 8) ( s - 4)( s - 3)( s - 2)
Step 4: Take the inverse transform of X :
4s + 9
First break - into partial fractions as
( s - 4)( s - 2)
13 - 4s A B C
= + +
( s - 4)( s - 2) s - 4 s - 3 s - 2
Using the cover-up rule, we have
2s - 5 2s - 5 3
A = lim(s - 4) = lim = ,
s 4 ( s - 4)( s - 3)( s - 2) s 4 ( s - 3)( s - 2) 2
2s - 5 2s - 5
B = lim( s - 3) = lim = -1,
s 3 ( s - 4)( s - 3)( s - 2) s 3 ( s - 4)( s - 2)
2s - 5 2s - 5 1
C = lim( s - 2) = lim =- .
s 2 ( s - 4)( s - 3)( s - 2) s 4 ( s - 3)( s - 4) 2

Hence
3 1 1 1 1
X = - -
2 s -4 s -3 2 s -2

11
and therefore
3 4t 1
x(t ) = e - e 3t - e 2 t .
2 2

12
Example 9
d2x dx dx
Solve the equation - 2 + 5 x = e 2t
, given that x = 0 and = 0 when t = 0.
dt 2 dt dt

In terms of of Laplace tyransform, this equation can be re-written as


1
s 2 X - sx0 - x1 - 2 sX + 2 x0 + 5 X = .
s-2
On inserting the initial conditions, we have
1
( s 2 - 2 s + 5) X = + 1.
s-2
On solving for X , we get
1 1
X = 2 +
s - 2s + 5 ( s - 2)( s - 2 s + 5)
2

Expanding the second term as partial fractions, we have


1 A Bs + C
= + 2
( s - 2)( s - 2 s + 5) s - 2 s - 2 s + 5
2

Using the cover-up rule, we have


1 1
A = lim( s - 2) = .
s 2 ( s - 2)( s - 2 s + 5) 5
2

With this value of the coefficient, we hav


1 (1/ 5) Bs + C [(1/ 5) + B]s 2 - [(2 / 5) + 2 B - C ]s + 1 - 2C
= + =
( s - 2)( s 2 - 2 s + 5) s - 2 s 2 - 2 s + 5 ( s - 2)( s 2 - 2 s + 5)
Comparing the coefficients in the numerators, we get
1 2
+ B = 0, + 2 B - C = 0, 1 - 2C = 1.
5 5
Solving this system of equations, we get
1
B = - , C = 0.
5
Hence
1 1 1 1 s
X = + 2 -
5 s - 2 s - 2s + 5 5 ( s - 2s + 5) 2

By noting that s 2 - 2 s + 5 = ( s - 1)2 + 4, we get


1 1 1 1 s -1 1 1
X = + - -
5 s - 2 ( s - 1) + 4 5 ( s - 1) + 4 5 ( s - 1) 2 + 4
2 2

1 1 1 4 1 s -1
= + -
5 s - 2 5 ( s - 1) + 4 5 ( s - 1) 2 + 4
2

Taking the inverse Laplace transform, we have


1 2 1
x(t ) == e 2t + et sin 2t - et cos 2t.
5 5 5
Solving Simultaneous Equations Using Laplace Transforms

Consider solving the system of equations

13
dx
+ 4 x + 5 y = 7 cos 2t
dt
, x = y = 0, when t = 0.
dy
- 4 y - 5 x = 8cos 2t
dt
Writing the equations in terms of Laplace transforms, we have
s
sX + 4 X + 5Y = 7 2 ,
s +4
s
sY - 4Y - 5 X = 8 2 ,
s +4
or
s
( s + 4) X + 5Y = 7 2 ,
s +4
s
( s - 4)Y - 5 X = 8 2 .
s +4
Multiplying the first equation by s - 4 and the second equation by -5 , we have
s ( s - 4)
( s + 4)( s - 4) X + 5( s - 4)Y = 7 2 ,
s +4
s
-5( s - 4)Y + 25 X = -40 2 .
s +4
Adding the two expressions, we get
7 s 2 - 68s
[( s + 4)(s - 4) + 25] X = .
s2 + 4
Solving for X , we get
7 s 2 - 68s
X = .
( s 2 + 4)( s 2 + 9)
Noting that s 2 + 4 = ( s + 2 j )( s - 2 j ) and s 2 + 9 = ( s + 3 j )( s - 3 j ) , we can expression the
right-hand side as partial fractions and thus have
7 s 2 - 68s A B C D
= + + + .
( s + 4)( s + 9) s + 2 j s - 2 j s + 3 j s - 3 j
2 2

Invoking the cover-up rule, we have


7 s 2 - 68s 1
A = lim = - 5 (34 + 7 j ),
s -2 j ( s - 2 j )( s 2 + 9)

7 s 2 - 68s 1
B = lim = - 5 (34 - 7 j ),
s 2 j ( s + 2 j )( s 2 + 9)

7 s 2 - 68s 1
C = lim = 10 (68 + j 21),
s -3 j ( s - 3 j )( s 2 + 4)

7 s - 68s 1
2
D = lim = 10 (68 - j 21),
s 3 j ( s + 3 j )( s 2 + 4)

Hence

14
1 (34 + 7 j ) 1 (34 - 7 j ) 1 (68 + 21 j ) 1 (68 - 21 j)
X =- - + +
5 s+2j 5 s-2j 10 s + 3 j 10 s - 3 j
68 s 28 1 68 s 63 1
=- - + +
5 s + 4 5 s + 4 5 s + 9 5 s2 + 9
2 2 2

Taking the inverse transform, we have


68 14 68 21
X = - cos 2t - sin 2t + cos 3t + sin 3t.
5 5 5 5

On the other hand, had we multiplied the first equation by -5 and the second
equation by s + 4 , we would have
s
-5( s + 4) X - 25Y = -35 2 ,
s +4
s( s + 4)
( s - 4)(s + 4)Y - 5( s + 4) X = 8 2 .
s +4
On subtracting the first expression from the second and solving for Y , we then
find that
8s 2 + 67 s
Y = 2 .
( s + 4)( s 2 + 9)
Next we express the left-hand side as partial fractions and thereby have
8s 2 + 67 s A1 B1 C1 D1
= + + + .
( s + 4)( s + 9) s + 2 j s - 2 j s + 3 j s - 3 j
2 2

Using the cover-up rule, we have


8s 2 + 67 s -32 - j134 1
A1 = lim
s -2 j ( s - 2 j )( s 2 + 9)
= (-4 j )(5) = 10 ( 67 - j16 ) ,

8s 2 + 67 s -32 + j134 1
B1 = lim
s 2 j ( s + 2 j )( s 2 + 9)
= (4 j )(5) = 10 ( 67 + j16 ) , .

8s 2 + 67 s -72 - j 201 1
C1 = lim
s -3 j ( s - 3 j )( s 2 + 4)
= ( -6 j )( -5) = - 10 ( 67 - j 24 ) ,

8s + 67 s -72 + j 201
2
1
D1 = lim = = - ( 67 + j 24 ) .
s 3 j ( s + 3 j )( s + 4)
(6 j )( -5)
2
10
With these coefficients, we then have
8s 2 + 67 s
Y = 2
( s + 4)( s 2 + 9)
1 67 - j16 1 (67 + j16) 1 67 - j 24 1 67 + j 24
= + - -
10 s + 2 j 10 s - 2 j 10 s + 3 j 10 s - 3 j
67 s 32 s 67 s 72 s
= - - +
5 s + 4 5 s + 4 5 s + 9 5 s2 + 9
2 2 2

Taking the inverse, we have


67 16 67 24
y (t ) = cos 2t - sin 2t - cos 3t + sin 3t.
5 5 5 5

Alternatively, having obtained the transforms


7 s 2 - 68s
X = 2
( s + 4)( s 2 + 9)

15
and
8s 2 + 67 s
Y = 2 ,
( s + 4)( s 2 + 9)
we could instead express them in partial fractions as
7 s 2 - 68s As + B Cs + D
X = 2 = 2 + 2
( s + 4)( s + 9) s + 4
2
s +9
and
8s 2 + 67 s A s + B1 C1 s + D1
Y = 2 = 12 + 2 ,
( s + 4)( s + 9)
2
s +4 s +9
Putting the right-hand terms under over the same denominators, we would
then have
7 s 2 - 68s ( A + C ) s 3 + ( B + D) s 2 + (9 A + 4C ) s + (9 B + 4 D)
X = 2 =
( s + 4)( s 2 + 9) ( s 2 + 4)( s 2 + 9)
and
8s 2 + 67s ( A1 + C1 ) s 3 + ( B1 + D1 ) s 2 + (9 A1 + 4C1 ) s + (9 B1 + 4 D1 )
Y = 2 = ,
( s + 4)( s 2 + 9) ( s 2 + 4)( s 2 + 9)
Equating coefficients of the various powers of s, we have
A + C = 0, B + D = 7, 9 A + 4C = -68 , 9 B + 4 D = 0.
A1 + C1 = 0, B1 + D1 = 8, 9 A1 + 4C1 = 67 , 9 B1 + 4 D1 = 0.
Solving this system of equations, we have
68 28 68 63
A=- , B=- , C = , D= ,
5 5 5 5
67 32 67 72
A1 = - , B1 = - , C1 = , D1 = ,
5 5 5 5
In this way, we would then find that
(-68 / 5) As + ( -28 / 5) (68 / 5) s + (63 / 5)
X = +
s2 + 4 s2 + 9
68 s 28 1 68 s 63 1
=- - + +
5 s + 4 5 s + 4 5 s + 9 5 s2 + 9
2 2 2

and
(-67 / 5) s + (-32 / 5) (67 / 5) s + (72 / 5)
Y = +
s2 + 4 s2 + 9
,
67 s 32 1 67 s 72 1
=- - + +
5 s2 + 4 5 s 2 + 4 5 s2 + 9 5 s2 + 9
Looking up the inverses then, we have
68 14 68 21
x(t ) = - cos 2t - sin 2t + cos 3t + cos 3t
5 5 5 5
and
67 16 67 24
Y = - cos 2t - sin 2t + cos 3t + sin 3t. ,
5 5 5 5

16